Some Implications of Interfaith Perceptions, Patterns of Belief, and Perceptions of Church Structure - Davidson, James D. (Sociological analysis, 1967)
One of the most significant developments in American religion during the past several decades has been the increased amount of interfaith communication. In this paper the authors explore some of the implications that 1) interfaith perceptions, 2) patterns of belief, and 3) perceptions of church structure may have for the ability of Christian groups to collaborate more effectively. The authors also raise other questions for research regarding these three variables.